Global risk assessment and strategic planning : an introduction and facilitator's guide to the GRASP methodology - McLaughlin, John; Ocock, Michael; Oldfield, Agi; Trebes, Barry (ICE Publishing, 2016)
'Global Risk Assessment and Strategic Planning' is a customised reference tool for project managers, encompassing risk-based management planning techniques and strategic decision-making processes for the successful management of projects, whether large or small. Making extensive use of front end strategic planning and risk assessment to stimulate teamwork, the methodology combines multi-stakeholder perspectives to enhance both the management team's knowledge base and its awareness of a project's situation. It facilitates not only the identification of potential risks to projects, but also provides an effective process for managing such risks.